Етіопатогенетичні особливості перебігу рецидивного афтозного стоматиту: сучасні підходи до профілактики та лікування - Ганчев, Кирило Сергійович; Кокарь, Оксана Олександрівна; Hanchev, K. S.; Kokar, O. O. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – аналіз відомостей фахової літератури щодо патогенетичних варіантів рецидивного афтозного стоматиту та підходів до його лікування, профілактики. Здійснили огляд сучасних досліджень щодо основних етіопатогенетичних механізмів виникнення та прогресування захворювання, навели чинні рекомендації щодо терапевтичних підходів до лікування та профілактики. Висновки. Досі немає єдиної лікувальної терапії рецидивного афтозного стоматиту, тому доцільними є систематизація, дослідження методик профілактики та лікування цієї патології, зокрема щодо полегшення болю, прискорення загоєння виразок, зменшення частоти та полегшення тяжкості його епізодів. Recurrent aphthous stomatitis (RAS) is an inflammatory disease of the oral mucosa, which has a chronic course with periods of remission and exacerbations. RAS requires adequate diagnosis for the purposes of properly treating. The study on RAS remains relevant over many years and continues to be a priority in modern dentistry. The aim of the work is to analyze the information in the professional literature on pathogenetic variants of RAS and approaches to its treatment and prevention. Despite the variety of studies, the etiology and pathogenesis of the disease remain the subject of numerous discussions. This article provides a review of current research on the main etiopathogenetic mechanisms of the disease development and progression, specifies current recommendations for therapeutic approaches to treatment and prevention. Conclusions. To date, there is no definitive therapeutic tactic for recurrent aphthous stomatitis, so it is advisable to systematize and study methods for the prevention and treatment of this pathology, including pain relief, acceleration of ulcer healing and reduction of its episode frequency and severity. Considering the etiopathogenetic variant of the disease development (metabolic disorders, stress, allergies, etc.), preventive measures should be comprehensive and include oral hygiene, a sparing diet, multivitamin and micro-, macroelement complexes, etc.
Etiopathogenetic features of recurrent aphthous stomatitis: modern approaches to prevention and treatment
Ганчев К. С. - ORCID ID: 0000-0002-5878-7980; Кокарь О. О. - ORCID ID: 0000-0001-7195-6999.
Keywords: афтозний стоматит; рецидив; лікування; стоматологічна профілактика; афти; виразки ротової порожнини; aphtho us stomatitis; recurrence; treatment; dental prophylaxis; aphthae; mouth ulcers